Ludicidade na aprendizagem da docência universitária e suas influências no desenvolvimento profissional docente - David, Maria Leticia de Sousa (2024)
Experiences that integrate the reason with the emotion are ludic experiences. They are those full of meaning for who he/she acts. Being like this, this study, has as general problem: what implications does the playfulness have for the learning of the academical teaching and for the educational professional development? And as general objective: to understand the implications of the playfulness for the learning of the academical teaching and for the educational professional development. For this, the studies regarding the playfulness concepts, innovation, teachers' initial formation, academical teaching, educational professional development, pedagogic practice and learning of the teaching are indispensable, once they allow to notice the conceptions that govern the educational performance in the Superior Education by the playfulness. The principal authors that based that research were: Almeida (2014), André (2016), Of Ávila and Fortune (2018), García (1999), Huizinga (2019), Imbernón (2011) (2012), Kishimoto (2011), Libâneo (1992), Luckesi (2022), Pepper and Anastasiou (2014), Rau (2012), Schiller (1989), Simeoni (2017), Tardif (2010), Veiga and Of Ávila (2010), Veiga (2004) and Vigotsky (2007). In that sense, he/she was considered as pertinent methodology to this study a research of qualitative approach, following the inductive method and of type ethnomethodological, Coulon (1995). As instrument of collection of data was used questionnaires and interviews. As subject of this research, teachers of the course of Pedagogy of University of Education of Itapipoca are had - FACEDI/UECE. The results of this investigation revealed that the academical teachers understand that starting from your own growth, of your autonomy, better he/she can understand your students, he/she wants they are academical or children and young coming of the school space. In view of that, in the formation of the teacher joking it is necessary to guarantee that these futures teachers have the concern in assuring the children's childhood, considering them as a historical subject and of rights. Therefore, the playfulness needs to do part of the teacher's formation and, in a more specific way, of the professional that will act with children, once playing is an axis of the pedagogic work. By these aspects, for the teacher to live and believe in activities that stimulate the creativity it is necessary that has verified the importance of these activities for the attainment of the objectives proposed in class room and it is done important to recognize also that the activities, denominated of ludic, they can be non ludic to depend of the feelings that are made presents on whom it is participating in them. Therefore, the playfulness that is an experience it interns to the subject, it can only be noticed and expresses for the subject that lives her. Therefore, in the academical teaching, the opportunity is enlarged of growing formative experiences, because the existence of the teaching is had, of the research and of the extension, as well as of knowledge production, in the research, and sharing of the results of the researches, what also needs to make possible motivating experiences, that integrate the different human dimensions, to meditate so much the cognitive aspect as the socioemotional. Finally, starting from the playfulness it can become the professional educational development based in interdisciplinarity beginnings, contextualization, democratization, pertinence and social relevance, ethics and affective and aesthetic sensibility.